TEMPI Syndrome: Update on Clinical Features, Management, and Pathogenesis - Xu, Jian; Liu, Wenqi; Fan, Fengjuan; Zhang, Bo; Zhao, Fei; Hu, Yu; Sun, Chunyan (Frontiers in Endocrinology, 2022)
TEMPI (telangiectasias, elevated erythropoietin level and erythrocytosis, monoclonal gammopathy, perinephric fluid collections, and intrapulmonary shunting) syndrome is a rare and newly defined multisystemic disease, which belongs to “monoclonal gammopathy of clinical significances”. Due to its rarity, the etiology, pathogenesis, and clinical features of this disease remain largely unknown. Owing to its hidden and diverse clinical manifestations, missed diagnosis and misdiagnosis are common. In recent years, as more patients (including three fatal cases) were identified, some special clinical manifestations other than the typical pentad of TEMPI syndrome have been reported. Meanwhile, several studies attempting to identify the pathogenesis of TEMPI syndrome were conducted. In this review, we summarize the reported clinical characteristics of TEMPI syndrome and discuss the current and potential treatment options for patients with TEMPI syndrome, including those with relapsed/refractory disease. Furthermore, we provide an overview of current knowledge on the pathophysiology of TEMPI syndrome.